Processing-dependent stabilization of a dissimilar rare-earth boride in high-entropy (Ti0.2Zr0.2Hf0.2Ta0.2Er0.2)B2 with enhanced hardness and grain boundary segregation. Issue 12 (September 2022) - Qin, Mingde; Shivakumar, Sashank; Lei, Tianjiao; Gild, Joshua; Hessong, Esther C.; Wang, Haoren; Vecchio, Kenneth S.; Rupert, Timothy J.; Luo, Jian
Abstract: This study demonstrates that 20% of a rare-earth (RE) diboride (ErB2 ) can be stabilized in a high-entropy transition metal (TM) diboride, despite the dissimilar chemical properties of RE and TM elements and large differences in lattice parameters of ErB2 and typical TMB2 . However, the phase formation depends on the fabrication route, which is a noteworthy observation. Specifically, single-phase (Ti0.2 Zr0.2 Hf0.2 Ta0.2 Er0.2 )B2 is synthesized via reactive spark plasma sintering (SPS) using elemental boron and metal elements. In contract, a specimen made by borocarbothermal reduction of binary oxides and SPS possess significant amounts of two Er-rich secondary phases. Notably, the RE addition in high-entropy TM diboride leads to improved hardness. Aberration-corrected scanning transmission electron microscopy (AC STEM) and energy-dispersive X-ray spectroscopy (EDS) elemental analyses further reveal significant Er segregation at grain boundaries. This work suggests that high-entropy ceramics can have significant solubilities of dissimilar components that may enable new, tunable, and improved properties. Highlights: 20% rare-earth Er can be stabilized in a high-entropy transitional metal boride. Single-phase (Ti0.2 Zr0.2 Hf0.2 Ta0.2 Er0.2 )B2 achieved via boron-metal reactive SPS. Phase formation in (Ti0.2 Zr0.2 Hf0.2 Ta0.2 Er0.2 )B2 depends on the fabrication route. The RE addition enhances the hardness of (Ti0.2 Zr0.2 Hf0.2 Ta0.2 Er0.2 )B2 . Larger Er atoms segregate at grain boundaries.